Bank Sampah Sebagai Salah Satu Strategis Alternatif Pengelolaan Sampah Berbasis Masyarakat di Desa Sesaot - Handayani Rinuastuti; Akhmad Saufi; Thatok Asmony; Handry Sudiartha (Universitas Mataram, 2019)
Plastic waste has become people’s main problems in Indonesia, both in cities and rural areas. Sesaot is one of three villages, together with Buwun Sejati and Pakuan Village, developed for sustainable tourist destination. As a tourist icon of Lombok Barat Distric, Sesaot villagers are responsible for keeping the village cleaned. Most people in Sesaot are ignorant of waste management, yet, some efforts are made individually. People are unaware of the economic value of waste management. Waste is percieved as unwanted and discarded residues. Such condition challanges efforts for sustainable tourism. The community service is aimed at directing local communities to participative waste management; encouraging the emergence of collaborative waste management; introducing waste bank model; and initiating the formation of community-based integrated waste management groups. The community service is organised through training and mentoring activities to sellected participants. . Expected results including; (1) the participants acquire knowledge of economic value of waste; (2) the participants form groups to start-up village waste bank.